2017
DOI: 10.1186/s13104-017-2512-1
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility pattern of Shigella spp. isolated from children under 5 years of age attending tertiary care hospitals, Nepal along with first finding of ESBL-production

Abstract: Background Shigella is an important cause of bacterial gastroenteritis in resource-poor countries. The treatment of shigellosis mostly requires antibiotics. However, the increase of multidrug resistance along with emergence of extended-spectrum β-lactamase and ciprofloxacin resistance among Shigella spp. has challenged the situation. This study was conducted to determine the distribution of species and antibiotic susceptibility pattern of Shigella species isolated from stool specimen among children less than 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 19 publications
(21 reference statements)
6
8
1
Order By: Relevance
“…Out of 653 studied cases, 25(3.82%) cases were Shigella positive. This isolation rate is comparable to a study done in Tribhuvan University Teaching Hospital and Kanti Hospital (2.1% culture positive) (Dhital et al, 2017). In contrast to our findings, two different studies conducted in Nepal reported a relatively higher prevalence rate (13.61% and 10.8%) (Wilson et al, 2006;Khan et al, 2014).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Out of 653 studied cases, 25(3.82%) cases were Shigella positive. This isolation rate is comparable to a study done in Tribhuvan University Teaching Hospital and Kanti Hospital (2.1% culture positive) (Dhital et al, 2017). In contrast to our findings, two different studies conducted in Nepal reported a relatively higher prevalence rate (13.61% and 10.8%) (Wilson et al, 2006;Khan et al, 2014).…”
Section: Discussionsupporting
confidence: 83%
“…Similarly, Nalidixic acid is a drug of choice in developing countries, and Ciprofloxacin in developed countries (Gharibi et al, 2012). The increased resistance (80% resistance) of Nalidixic acid was observed in the present study and other studies conducted in Nepal (Bhattacharya et al, 2005;Khan et al, 2014;Dhital et al, 2017). This increased resistance to Nalidixic acid in Nepal can be attributed to the over-the-counter availability of drugs, self-prescription by patients, and poor antibiotic policies.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…An antibiotic susceptibility test was performed on all bacterial isolates by the disc diffusion method.10 antibiotics were used in this study as in table (3).The results showed that all Shigella sonnei isolates were resistant to Nalidixic acid and Co-trimoxazole at a rate of 100%.The current study does not agree with the study of Abdel-Rahman et al, [24] in Baghdad, as the results showed that 54.23% of Shigella isolates are resistant to nalidixic acid. The results also showed that 93.3% of Shigella sonnei isolates were resistant to Ampicillin, this result agreed with the results of Subhash et al, [25] .While 93.3% of isolates were sensitive to chloramphenicol This result agreed with the findings of Siraj [26] as all Shigella sonnei isolates were resistant to this antibiotic. Azithromycin also showed a significant effect on Shigella sonnei isolates, as 93.3% of isolates were sensitive to this antibiotic.These results agreed with the results of the study conducted by Jomezadeh et al, [27] in Iran, as they indicated that all S.sonnei isolates are resistant to this antibiotic.Cefotaxime, Ceftriaxone,which belongs to cephalosporins group,showed convergent effects in their ability to inhibit S.sonnei isolates, as the results showed that73.4% of isolates were sensitive to Cefotaxime and 80% of isolates were sensitive to Ceftriaxone.…”
Section: Antibiotic Susceptibility Testsupporting
confidence: 90%
“…2017 ) and cephalosporins ( Mahmoudi et al . 2017 ) and multidrug ( Dhital et al . 2017 ) leading to the search for plant products ( Mirza et al .…”
Section: Introductionmentioning
confidence: 99%